2022
DOI: 10.1007/s00167-022-07018-y
|View full text |Cite
|
Sign up to set email alerts
|

Higher return to pre-injury type of sports after revision anterior ligament reconstruction with lateral extra-articular tenodesis compared to without lateral extra-articular tenodesis

Abstract: Purpose To evaluate the rate of return to pre-injury type of sports (RTS type) in patients after revision anterior cruciate ligament reconstruction (ACLR) with lateral extra-articular tenodesis (LET) compared to patients after revision ACLR without LET. Methods Seventy-eight patients who underwent revision ACLR with an autologous ipsilateral bone-patellar tendon-bone autograft with and without LET were included at least one year after surgery (mean follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 24 publications
3
23
0
Order By: Relevance
“…Recently, Boksh et al [44] investigated the effect of an anterolateral supplemental procedure in revision ACL‐R in a meta‐analysis. They included 10 comparative studies with a total of 793 patients [26, 31, 42, 45–51] and concluded that a lateral extra articular augmentation in ACL revision surgery could improve rotational stability, subjective IKDC scores, and reduce graft failure rate compared to isolated ACL revision.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Boksh et al [44] investigated the effect of an anterolateral supplemental procedure in revision ACL‐R in a meta‐analysis. They included 10 comparative studies with a total of 793 patients [26, 31, 42, 45–51] and concluded that a lateral extra articular augmentation in ACL revision surgery could improve rotational stability, subjective IKDC scores, and reduce graft failure rate compared to isolated ACL revision.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of complications remained low, with only one case (5.3%) experiencing residual pain and reoperation for a partial menisectomy. To date, few studies have analysed the results of revision ACLR and LET [12][13][14][15][16][17][18][19][20][21][22], with differences in graft type and surgical technique. Furthermore, selecting a uniform group of patients presents a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors [6,8,9,[11][12][13][14][15][16][17][18][19][20][21][22] already advocate the critical role of adding an extra-articular procedure due to its ability to restrict rotational laxity [6]. Getgood et al have recently found that adding LET to primary ACLR in young patients at high risk of failure results in a statistically significant reduction in graft rupture and persistent rotatory laxity two years after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations